Sufficiency of the Central Provident Fund in meeting healthcare and retirement needs : a comparison with selected countries. - Chew, Dominic Minzhong. (2008)
This paper aims to ascertain the adequacy of Singapore’s Central Provident Fund in providing for the healthcare and retirement needs of Singaporeans by comparing it with schemes in other countries. Through this, we hope to get a better picture of the robustness of the current CPF system, and generate practical recommendations to improve it.